The Effect of Virtual Reality in Nasogastric Catheter Application Training for Nursing Students: A Randomized Controlled Trial - Ayşe Eminoğlu Güven; Nazike Duruk; İbrahim Savran (Journal of Computer Assisted Learning, 2026)
ABSTRACT Background With advances in technology, innovative teaching methods are being used to teach nasogastric catheterization. Aim This study was conducted to evaluate the effects of training in nasogastric catheterization, delivered via traditional and virtual reality methods, on the knowledge, skills, self‐confidence, anxiety and motivation of final‐year nursing students. Methods This randomized controlled experimental design study was conducted with 78 fourth‐year nursing students (39 in the intervention group and 39 in the control group) between March and May 2024. Written permission was obtained from the ethics committee, the institution and the students. Data were collected via the ‘Personal Information Form’, ‘Nasogastric Catheterization Application Knowledge Test’, ‘Nasogastric Catheter Application Checklist’, ‘Self‐Confidence Visual Analog Scale’, ‘Anxiety Visual Analog Scale’ and ‘Instructional Material Motivation Scale for Single‐use’. All the students were trained according to the course content. After the training, the students in the intervention group used the virtual‐reality application, and the students in the control group used it with the traditional method. After the application, the students' skills were evaluated and post‐tests were applied. The data were evaluated using chi‐square analysis, independent‐samples t ‐tests and two‐way analysis of variance with repeated measures. Results There was no significant difference in knowledge and motivation scores between the intervention and control groups ( p > 0.05). The students in the intervention group had significantly greater nasogastric catheterization skills, critical procedure step scores and self‐confidence scores and lower anxiety scores than did those in the control group ( p < 0.05). Conclusion Virtual reality was more effective than traditional methods at improving students' nasogastric catheterization skills, increasing their self‐confidence and reducing their anxiety. Therefore, the use of virtual reality to teach psychomotor skills, such as nasogastric catheterization, should be expanded. Trial Registration ClinicalTrials.gov registration number was received as NCT05815979